Prothrombin G20210A Mutation and Lower Extremity Peripheral Arterial Disease: A Systematic Review and Meta-analysis. Issue 2 (August 2015) - Vazquez, F.; Rodger, M.; Carrier, M.; Le Gal, G.; Reny, J.-L.; Sofi, F.; Mueller, T.; Nagpal, S.; Jetty, P.; Gandara, E.
Abstract : Objective/Background: Despite being an important risk factor for venous thromboembolism, the role of the prothrombin G20210A mutation in patients with arterial disease remains unclear. The aim of this review was to evaluate the association of prothrombin G20210A and lower extremity peripheral arterial disease (PAD). Methods: This was a systematic review and meta-analysis of case–control studies. A systematic review of electronic databases, including MEDLINE and Embase, was conducted to assess the prevalence of prothrombin G20210A in patients with lower extremity PAD. The main outcome was the prevalence of prothrombin G20210A in patients with lower extremity PAD. The random effects model odds ratio (OR) was used as the primary outcome measure. Results: The initial electronic search identified 168 relevant abstracts of which five studies evaluating 1, 524 cases of PAD and 1, 553 controls were included. Prothrombin G20210A was found in 70 of 1, 524 patients with lower extremity PAD and 44 of 1, 553 of the controls (random effects OR 1.68, 95% confidence interval [CI] 0.8–3.2). In those with critical limb ischemia (CLI), the prevalence of prothrombin G20210A was 23 of 302 compared with 31 of 1, 253 of the controls (OR 3.2, 95% CI 1.6–6.1). Conclusion: Despite finding no significant association between lower extremity PAD and prothrombin G20210A, the meta-analysis suggests that the prevalence of prothrombin G20210A is significantly elevated in those with atherosclerotic occlusive disease of the lower extremities presenting with CLI. Well-designed prospective cohort studies evaluating the role of prothrombin G20210A as a predictor of disease progression or adverse vascular events are highly needed.